Review article: pathogenesis of Crohn's perianal fistula—understanding factors impacting on success and failure of treatment strategies. Issue 3 (19th June 2018) - Tozer, P. J.; Lung, P.; Lobo, A. J.; Sebastian, S.; Brown, S. R.; Hart, A. L.; Fearnhead, N.; ,
Summary: Background: Evidence from groups who have studied fistula aetiology and extrapolation from interventional studies supports a multifactorial hypothesis of Crohn's perianal fistula, with several pathophysiological elements that may contribute to fistula formation, persistence and resistance to treatment. Aim: An evidence synthesis of current understanding of pathophysiological factors underlying Crohn's perianal fistula is presented, exploring the fundamental reasons why some treatments succeed and others fail, as a means of focussing clinical knowledge on improving treatment of Crohn's perianal fistula. Methods: Evidence to support this review was gathered via the Pubmed database. Studies discussing pathophysiological factors underpinning perianal fistula, particularly in Crohn's disease, were reviewed and cross‐referenced for additional reports. Results: Pathophysiological factors that impact on success or failure of interventions for Crohn's perianal fistulae include the high‐pressure zone, obliterating the dead space, disconnecting the track from the anus, removing epithelialisation, eradicating sepsis and by‐products of bacterial colonisation, correcting abnormalities in wound repair and removing the pro‐inflammatory environment which allows fistula persistence. Most current interventions for Crohn's perianal fistulae tend to focus on a single, or at best two, aspects of the pathophysiology of Crohn's anal fistulae; as a result, failure to heal fully is common. Conclusions: For an intervention or combination of interventions to succeed, multiple factors must be addressed. We hypothesise that correct, timely and complete attention to all of these factors in a multimodal approach represents a new direction that may enable the creation of an effective treatment algorithm for Crohn's anal fistula.